Sociopathic Characteristics of Henry Winter in Donna Tartt’s The Secret History: A Psychological Reading - Denisa Budi Sulistianingtyas; Arif Rokhman (Lexicon, 2026)
This research examines the character of Henry Winter in The Secret History by Donna Tartt. It aims to support the interpretation by analyzing Henry’s sociopathic characteristics and his manipulation pattern toward other characters throughout the novel. The researcher proceeds to apply Cleckley’s characteristics of sociopathy to analyze Henry Winter. To account for the novel’s first-person narration, the analysis incorporates Genette’s focalization theory (1972) and Minderop’s theory of characterization (2005) to extract the data. The findings reveal that Henry Winter exhibits seven interrelated sociopathic characteristics: 1) superficial charm and 'good' intelligence, 2) absence of delusions or irrationality, 3) absence of nervousness, 4) untruthfulness, 5) lack of remorse, 6) unreliability, and 7) suicide as a cover for his irresponsibility, presented as self-sacrifice. The narrative’s theatrical elements, which show classical sacrificial symbolism, bridge scientific psychology with literary interpretation. The findings show that Henry's manipulations are layered through those seven characteristics. This research then contributes significantly to psychoanalytic literary criticism and broadens academic discourse on The Secret History.